Discrimination of the Social Parasite Ectatomma parasiticum by Its Host Sibling Species (E. tuberculatum). (6th June 2013) - Fénéron, Renée; Poteaux, Chantal; Boilève, Marie; Valenzuela, Jorge; Savarit, Fabrice
Abstract : Among social parasites, workerless inquilines entirely depend on their host for survival and reproduction. They are usually close phylogenetic relatives of their host, which raises important questions about their evolutionary history and mechanisms of speciation at play. Here we present new findings on Ectatomma parasiticum, the only inquiline ant described in the Ectatomminae subfamily. Field data confirmed its rarity and local distribution in a facultative polygynous population of E. tuberculatum in Mexico. Genetic analyses demonstrated that the parasite is a sibling species of its host, from which it may have diverged recently. Polygyny is suggested to have favored the evolution of social parasite by sympatric speciation. Nevertheless, host workers from this population were able to discriminate parasites from their conspecifics. They treated the parasitic queens either as individuals of interest or as intruders, depending on their colonial origin, probably because of the peculiar chemical profile of the parasites and/or their reproductive status. We suggest that E. parasiticum could have conserved from its host sibling species the queen-specific substances that produce attracting and settling effect on workers, which, in return, would increase the probability to be detected. This hypothesis could explain the imperfect social integration of the parasite into host colonies.